Autonomous Underwater Vehicle Operations - Needs of New Users. - Bose, N; Hayes, D; Griffiths, G (National Oceanography Centre, Southampton. Society for Underwater Technology London, 2007)
To date most autonomous underwater vehicle (AUV) operators have also been heavily involved in the development of the vehicles, but as the technology matures, increasingly more users are becoming involved in operations and these operators see the AUVs primarily as tools for industry/commercial and science missions. This chapter addresses the needs of new users making decisions on whether and how to operate AUV(s) within their organisation. The aspects considered include: personnel, funding, insurance and safety. Personnel issues include recruitment, skills and education, training and management. Funding is required for capital, operating, maintenance and repairs, upgrades and replacement. Insurance is a large cost item and is affected by the very small numbers of users. Safety issues include safety of the vehicle itself and safety of others due to operations of the vehicle: loss and recovery, damage during launch, collisions, operating protocols, regulations and legal issues, operating personnel and support vessels.